2018
DOI: 10.1007/s10517-018-4040-y
|View full text |Cite
|
Sign up to set email alerts
|

fMRI Responses in Healthy Individuals and in Patients with Mild Depression to Presentation of Pleasant and Unpleasant Images

Abstract: Patients with mild depression and apparently healthy individuals were presented images and asked to sort them into "pleasant" and "unpleasant" subsets. In both groups, the main differences between brain activation patterns during presentation of pleasant and unpleasant images were localized in the motor regions (precentral and postcentral gyrus) and in the cerebellum (p<0.05 with FWE correction). Most likely, these clusters are associated with motion (pressing a button in accordance with the instruction). Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The inferior frontal gyrus (IFG) has been typically implicated in behavioral inhibition (right IFG, Aron et al, 2003; Duann et al, 2009), and its activity in depression is thought to reflect response to treatment (Dai et al, 2020; Gorka et al, 2019; Marwood et al, 2018). Moreover, while some studies have also reported changes in the activity of the parietal cortex in major depressive disorder (41,42), it is more likely that our neuroimaging finding is related more to its role in evidence accumulation. Human (4345) and non-human primate (4649) research has shown that the parietal cortex is the site of evidence accumulation in decision-making tasks.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The inferior frontal gyrus (IFG) has been typically implicated in behavioral inhibition (right IFG, Aron et al, 2003; Duann et al, 2009), and its activity in depression is thought to reflect response to treatment (Dai et al, 2020; Gorka et al, 2019; Marwood et al, 2018). Moreover, while some studies have also reported changes in the activity of the parietal cortex in major depressive disorder (41,42), it is more likely that our neuroimaging finding is related more to its role in evidence accumulation. Human (4345) and non-human primate (4649) research has shown that the parietal cortex is the site of evidence accumulation in decision-making tasks.…”
Section: Discussionmentioning
confidence: 75%
“…This result raises an interesting possible clinical application. Attentional biases in stimulus processing have been suggested to be causally involved in depression and risk of depression relapse (6,7 (41,42), it is more likely that our neuroimaging finding is related more to its role in evidence accumulation. Human (43)(44)(45) and non-human primate (46)(47)(48)(49) research has shown that the parietal cortex is the site of evidence accumulation in decision-making tasks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The average age of participants ranged from 15 to 66 years old, and only 2 studies ( 40 , 55 ) focused on youths with depression. Depressive patients in 20 studies ( 17 19 , 40 47 , 49 , 50 , 52 55 , 57 , 59 , 61 ) were diagnosed according to the DSM, 1 ( 37 ) in the light of CCMD, and 2 ( 51 , 58 ) based on ICD; 3 studies applied DSM-IV and CCMD-3 ( 38 , 39 , 60 ); 1 used both DSM-IV and ICD-10 ( 56 ); 1 adopted CCMD-3 and ICD-10 ( 48 ). Hamilton Depression Rating Scale, Beck Depression Inventory, Montgomery–Asberg Depression Scale, Center for Epidemiologic Studies Depression Scale, and Children's Depression Rating Scale-Revised were adopted to screen depression.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Lan et al observed that MDD group had higher fALFF value in the right MFG ( 49 ). The MDD patients with somatic symptoms exhibited lower ReHo value in the right MFG ( 50 ) and the depressive patients had less pronounced activation of MFG in response to both positive and negative images ( 51 ). Several studies found that the abnormal interhemispheric homotopic functional connectivity in the bilateral MSFG and MFG in different types of depressive group, such as MDD with and without anhedonia, recurrent MDD and MDD with gastrointestinal symptoms ( 52–54 ).…”
Section: Discussionmentioning
confidence: 99%